Sengketa Akad Murabahah Pada Bank Muamalat Tbk. Kantor Cabang Darmo Surabaya Menurut Perspektif Hukum Ekonomi Syariah - Bunayan, Hujaidi (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2018)
One of the concepts of fiqh muamalah which is widely practiced by Islamic banking is akad (agreement) murabaha trading. Akad is much in demand by sharia banking due to security factors and the lack of risk for Islamic banks than mudlarabah and musharaka contracts. Murabahah is a type of trading with the determinatin that are more specific than general trading. Murabaha is a part of sharia banking products. There are dispute between  the bank and its  custumers, there shall be alternatives to the dispute over the dispute. To the parties to the dispute may settle concensus  deliberation, thourgh dispute settlement institutions or through ligition proceedings within the courts set forth in the dispute resolution clause. Based on the background of the above problem, it can be formulated the problem  will be identified as follows (1)  How to dispute murabaha agrement on Bank Muamalat according to the perspektive of sharia economic law ? (2) How to settle Aqad (agreement) Murabaha dispute with Bank Muamalat Tbk. Darmo, Surabaya Branch Office ?The research method used in this research is normative juridical method with 2 (two) variants approach that is statute approach and conceptual approach. Source of data used are primary data covering material of primary law, secondary and tertiary.This study aimed to (1) analyze the dispute of aqad (agreement) murabaha at the Bank Muamalat according to the perspektive of sharia economic law; and (2) analyze and find the form settlement of aqad murabahah dispute in Bank Muamalat Tbk. Darmo, Surabaya Branc Office. This research is expected  to cuntribute thought or provide solutions in the field of law related to the application of Adaq Murabahah in  sharia banking institutions in Indinesia through theoretical analytics, be it from philosophical and sociological revew is expected to provide legal protection for customer  and Bank Muamalat Tbk. Darmo Surabaya branch office.The results of this study indicate that the findings of the murabahah dispute agreement at the Bank Muamalat Branch Office Darmo Surabaya according to the perspective of sharia economic law caused by the control of the business aspects of the contract. Settlement of Aqad Murabahah dispute with Bank Muamalat Tbk. Darmo Surabaya branch office is conducted by Settlement of dispute through litigation and non-litigation. The completion of disputes with litigation is done through the religious courts. The final result of a dispute completion through litigation is a verdict that states a win-lose solution. Non- completion can be identified by alternative dispute resolution (ADR) with arbitration, negotiation, mediation, conciliation, expert judgment and fact finding.The research method used in this research is normative juridical method with 2 (two) variants approach that is statuce approach and conceptual approach. Sources of data used are primary data that is literature data covering material of primary law, secondary and tertiary. Keywords : Akad, Dispute, Murabahah.